New development: Mitigating and negotiating the co-creation of dis/value—Elinor Ostrom's design principles and co-creating public value. Issue 1 (2nd January 2023) - Williams, Oli; Lindenfalk, Bertil; Robert, Glenn
IMPACT: This article provides a way to promote more effective and equitable collaboration in the design and delivery of public services. Increasingly public services are designed with service users, but it is common for these provider–user endeavours to perform sub-optimally and/or to have negative outcomes. The authors offer a set of principles and a novel framework for applying them that have been designed to: firstly, mitigate the potential for sub-optimal and/or negative performance and, secondly, promote more positive processes and outcomes for provider–user collaborations. Improving provider–user collaboration in this way will ultimately lead to better design and delivery of public services.